STRATEGI POLITIK BOBON SANTOSO DALAM PARTAI GERINDRA MENJELANG PILKADA 2024: ANALISIS BERDASARKAN TEORI PILIHAN RASIONAL - Apriliani, Desak Gede Ita; Noak, Piers Andreas; Pramana, Gede Indra (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2024)
Rational choice theory is a framework used in various fields, including economics, political science, and sociology, to explain how individuals make decisions. According to this theory, people are rational actors who weigh the potential benefits and costs of thei r actions before choosing the option that maximizes their personal advantage or utility. In essence, individuals evaluate available options based on their preferences and the expected outcomes, then select the course of action that provides the greatest perceived benefit. Rational choice theory assumes that people have access to relevant information, make decisions with clear preferences, and act consistently to achieve their objectives . Bobon Santoso's decision to join the Gerindra Party ahead of the Bali regional elections can be understood through the lens of rational choice theory, which emphasizes individual interest considerations. Bobon, who admires Prabowo Subianto as a dedicated figure, saw an opportunity to strengthen his political influence and support the party’s gubernatorial and vice-gubernatorial candidates for Bali. By joining, he gained access to a broader political network and increased his chances of political success. This decision reflects a rational strategy to maximize both political and personal gains within the context of the Bali elections.